DECLINE IN FRESHNESS OF SKIPJACK TUNA ALONG THE DISTRIBUTION CHAIN FROM LANDING SITES TO LOCAL CONSUMERS IN TERNATE: PENURUNAN KESEGARAN IKAN CAKALANG SELAMA DISTRIBUSI DARI TEMPAT PENDARATAN IKAN KE KONSUMEN LOKAL DI TERNATE - Rian Hidayat; Eko Sri Wiyono; Roza Yusfiandayani; Iin Solihin (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Proper handling of fish is a key factor influencing the success of fresh fish distribution and trade. However, in practice, handling procedures are often inadequately implemented by fishermen, resulting in reduced fish quality and price. To address this issue, a study was conducted at the Dufa-dufa Fish Landing, Ternate City (North Maluku) to assess the distribution and quality of fresh skipjack tuna (Katsuwonus pelamis). The distribution of fresh skipjack tuna is extensive, reaching all regions of the city through various fish distribution nodes. While fishermen have endeavored to maintain the freshness, quality degradation was observed along the distribution chain. Sensory tests were conducted at each stage of the distribution process, from landing to the final consumers, assessing organoleptic attributes such as eyes, gills, and body texture. The results showed that the values differ at each node and tended to decline. The Kruskal-Wallis analysis indicated a significant difference in organoleptic values between the eyes, gills, and body texture of skipjack tuna at each distribution node (P < 0.05). These findings suggested that the freshness of skipjack tuna may decline during the distribution process.